In Vitro Anthelmintic Activity of Abutilon Indicum (L.) Sweet And Abelmoschus Manihot (L.) Medik - Chumbhale, D. S.; Chaudhari, S. R.; Upasani, C. D. (Asian Journal of Pharmaceutical Research and Development, 2013)
The present study was designed to evaluate the anthelmintic potential of extracts of various parts of plant, Abutilon indicum (L.) Sweet (A. indicum) and Abelmoschus manihot (L.) Medik (A. manihot) are important medicinal plants in Indian traditional system of medicine. Methanol extract from the leaves, stems and roots of A. indicum and A. manihot were investigated for their anthelmintic activity against the earthworms, Pheritima posthuma. Each extract was studied in the bioassay at 20 mg/ml, which involved determination of time of paralysis and time of death of the worms. Both the extracts of both plants exhibited considerable anthelmintic activities, and the order of sensitivity of the extracts to the worms was stems > roots > leaves for the A. indicum and stems > roots > leaves for the A. manihot. The methanol extracts of stems of both A. indicum and A. manihot were found to be most active. Albendazole (20 mg/ml) and distilled water were included in the assay as a standard reference drug and control respectively. Present study of evaluation of anthelmintic potential of plants, A. indicum and A. manihot were found that methanolic extracts of both plants showed more prominent activity. These findings will be useful toward the better acceptability of these medicinal plants in therapeutics.